Attraction of Scarabaeinae (Coleoptera: Scarabaeidae) to different baits in the Brazilian Amazon region,Atracción de Scarabaeinae (Coleoptera: Scarabaeidae) por diferentes cebos en la región Amazónica Brasileña - Cajaiba, Reinaldo L. (2017)
Dung beetles (Coleoptera: Scarabaeidae: Scarabaeinae) are considered essential for enhancing the physicochemical characteristics of soils, principally by changing organic materials (e.g. dead animals, faeces, fruits e leaf litter). This study compared the species richness and abundance of dung beetles captured using various types of baits, to demonstrate attractiveness differences in variable habitats of the Brazilian Amazon. Samplings were carried out with pitfall traps baited with human faeces, rotten banana, rotten meat and a nonbaited trap, in February, March, June, September and October 2015. Habitats included native forests, agriculture areas, pastures and disturbed forests in different regeneration stages. A total of 13 736 Scarabaeinae beetles were captured, distributed over 98 species. Most individuals were captured using traps baited with faeces (76.7 % of individuals), followed by rotten meat baited traps (17.8 % of individuals), fermented banana baited traps (3.9 % of individuals) and finally by non-baited traps (1.6 % of individuals). A significant difference in attractiveness of the different baits used and habitats types was observed. Most of the captured assemblages were composed by coprophagous (42 %), generalist species (32 %), necrophagous (15 %) and none was classified as saprophagous. Approximately 54 % of the specimens were tunnelers, 25 % were rollers and 12 % were dwellers. The species of Scarabaeinae sampled in the region revealed qualitative and quantitative differences among their assemblages and the phytophysiognomies. The forest environments housed the greatest species richness observed, and a fraction of these is exclusive of those areas. We concluded that some species of Scarabaeinae have an important potential as disturbance indicators in the Amazonian ecosystem. Rev. Biol. Trop. 65 (3): 917-924. Epub 2017 September 01.